Death and the crown : ritual and politics in France before the Revolution - Byrne, Anne (Studies in modern French and Francophone history., 2020)
Looking at royal ritual in pre-revolutionary France, Death and the crown examines the deathbed and funeral of Louis XV in 1774, the lit de justice of November 1774, and the coronation of Louis XVI, including the ceremony of the royal healing touch for scrofula. It reviews the state of the field in ritual studies and appraises the status of the monarchy in the 1770s, including the recall of the parlements and the many ways people engaged with royal ritual. It answers questions such as whether Louis XV died in fear of damnation, why Marie Antoinette was not crowned in 1775 and why Louis XVI's coronation was not held in Paris. This lively, accessible text is a useful tool for under- and post-graduate teaching which will also be of interest to specialists on this under-researched period.